Causes of elevated parathyroid hormone levels in postmenopausal women - Esen, İrfan; Akturk Esen, Selin; Cander, Soner; Oz Gul, Ozen; Ocakoglu, Gokhan; Erturk, Erdinc (The European Research Journal, 2017)
Objective. In this study we aimed to investigate causes of hyperparathyroidism and related factors in postmenopausal women. Methods. The study was conducted on 156 postmenopausal women, 43 with normal serum parathyroid hormone (PTH) levels and 113 with elevated serum PTH levels. Serum levels of 25-OH vitamin D, calcium and phosphorus, 24-hour urine calcium, phosphorus and calcium/creatinine ratio were compared between study groups. Also, bone mineral density, age of menopause, educational level, occupation, clothing style, daylight exposure time and daily dietary calcium consumption of subjects and relationships of these parameters with parathyroid hormone levels were investigated.Results. Causes of elevated serum PTH level were vitamin D deficiency in 92.9% and primary hyperparathyroidism in 4.4% of study group. Serum PTH levels were significantly higher in housewives (p